The dual roles of immunity in ALS: Injury overrides protection - Benjamin J. Murdock; Diane E. Bender; Benjamin M. Segal; Eva L. Feldman (Neurobiology of Disease, 2015)
Amyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disease affecting motor neurons. Disease progression is accompanied by a multi-phased immune response, and recent studies indicate that the immune system is not simply a bystander during disease, but plays an active role in shaping ALS pathology. The role of the immune system during ALS progression is highly complex, however, as it has been found to have a role in both enhancing neurodegeneration as well as protecting the central nervous system. Previous reports have established that the immune response can therefore be separated into two distinct phases: a protective Type 2 response followed by a neurotoxic Type 1 response. This review will address the two phases of the immune response in ALS and describe their roles during disease progression. More importantly, it will also examine the likely sources of immune polarization that are responsible for shifting immunity from the protective T2 phase to the neurotoxic T1 phase.